2008
DOI: 10.3801/iafss.fss.9-957
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic risk analysis methodology for high-rise buildings taking into account fire department intervention time

Abstract: Fire safety regulations have a major impact on many aspects of the overall design of high-rise buildings, where complex and non-conventional architectural elements and designs can lead to fire environments diverging significantly from those used in the development of current codes and standards. Additionally, fire-fighting in high-rise buildings must be carried out from the inside of the building and fire-fighters must use stairwells or special fire-fighter lifts to access the floors which are on fire One way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The shorter mean distance travelled for category D fire stations could be an important factor for the significant reduction in response time in 2020. Yung (2008), Tómasson et al (2008), and Claridge and Spearpoint (2013) reported that one of the main factors influencing the response time was the distance travelled, where the city centre recorded average speeds of approximately 20 km/h for a short distance compared to 70 km/h on state highways for longer distances.…”
Section: Fire Incidents Of the Selected Stationsmentioning
confidence: 99%
“…The shorter mean distance travelled for category D fire stations could be an important factor for the significant reduction in response time in 2020. Yung (2008), Tómasson et al (2008), and Claridge and Spearpoint (2013) reported that one of the main factors influencing the response time was the distance travelled, where the city centre recorded average speeds of approximately 20 km/h for a short distance compared to 70 km/h on state highways for longer distances.…”
Section: Fire Incidents Of the Selected Stationsmentioning
confidence: 99%